THE TIME LAPSE FOR THE EXERCISE OF THE INHERITANCE PETITION ACTION: LEGAL, DOCTRINAL AND JURISPRUDENTIAL ASPECTS (REMUNOM, 2025)
The main objective of this study is to analyze the consequences of the fluctuations caused by the opinions of the two panels of the Second Section of the Superior Court of Justice (STJ) regarding the gap in the beginning of the prescriptive term for filing an inheritance petition, provided for in articles 1,824 to 1,828 of the Civil Code, with a focus on actions involving the recognition of paternity post mortem, in order to elucidate the doctrinal concepts of the inheritance petition, its procedure and prescriptive term, in addition to addressing inheritance law and its types. Next, the relationship with the principle of Legal Certainty and the way in which the divergence in case law between the third panel and the fourth panel of the Second Section of the STJ interfere in Brazilian legal relations will be analyzed, in order to weigh the different positions.